1994
DOI: 10.1038/hdy.1994.153
|View full text |Cite
|
Sign up to set email alerts
|

The estimation of the genetic correlation: the use of the jackknife

Abstract: To understand fully the process of evolution of quantitative traits it is necessary to be able to estimate the genetic correlation and its associated standard error. At present, estimation methods are available only for relatively simple designs. An alternative procedure is to use the correlation of family means as an estimate of the genetic correlation. We evaluate the utility of the family mean method and that of the more general procedure, the jackknife. The family mean method is shown to be potentially ver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
123
0
1

Year Published

1995
1995
2013
2013

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 121 publications
(125 citation statements)
references
References 16 publications
1
123
0
1
Order By: Relevance
“…This method of estimation is approximate as both the genetic covariance and variance may be biased by within-family (environmental) effects (Via, 1991;Roff & Preziosi, 1995). Such potential contamination, however, is not likely to influence the comparison of the genetic correlations between the insecticide-treated and insecticide-free populations.…”
Section: Discussionmentioning
confidence: 99%
“…This method of estimation is approximate as both the genetic covariance and variance may be biased by within-family (environmental) effects (Via, 1991;Roff & Preziosi, 1995). Such potential contamination, however, is not likely to influence the comparison of the genetic correlations between the insecticide-treated and insecticide-free populations.…”
Section: Discussionmentioning
confidence: 99%
“…Using simulation models, Roff and Preziosi (1994) showed that this jacknife approach provides better genetic estimates than those based on conventional inbred line means when the number of inbred lines contained in the analysis is small (o20 lines). It is important to note that estimates of genetic (co)variance from inbred lines contain variance because of dominance and/or epistasis and therefore should be considered broad-sense estimates (Falconer and Mackay, 1996).…”
Section: Statistical Analysesmentioning
confidence: 99%
“…where S N,i is the ith pseudo-value, r N is the genetic correlation estimated using the means of all N inbred lines, and r NÀ1,i is the genetic correlation obtained by dropping the ith inbred line alone (Roff and Preziosi, 1994). The jacknife estimate of the genetic correlation (r j ) is then simply the mean of the pseudo-values, and an estimate of the standard error (s.e.)…”
Section: Statistical Analysesmentioning
confidence: 99%
See 1 more Smart Citation
“…The genetic correlation estimate, r g , reported in (a) is that provided by method 1, and the one reported in (b) is that of method 3. they are inflated by the error variance; this is analogous to the contamination of the productmoment correlation of genotypic means. The contaminating term is 2 divided by r, so the higher the number of replicates, the less the contamination (Via, 1984;Roff & Preziosi, 1994). To provide a method also valid in small samples, we developed an adjustment for the inflation by subtracting the error mean square divided by r from each of the two genetic variances before computing the geometric mean in eqn (4).…”
Section: Methodsmentioning
confidence: 99%